Clinical comparison in the remote management of bronchial asthma during the COVID-19 pandemic between two controller therapies: Fluticasone and beclomethasone - Recabarren Lozada, Arturo Felipe (2024)
Objective: To compare the level of asthma control using the Asthma Control Test (ACT) and clinical manifestations in two groups of patients treated with different inhaled corticosteroids (ICG). Materials and methods: Descriptive, observational and prospective study in which the level of asthma control was recorded in 521 children in the asthma programme of Hospital III Yanahuara (Arequipa, Peru), during the period from June 2020 to December 2021, by means of remote consultation using the ACT and the collection of clinical findings (daytime and night-time symptoms, emergency visits and the use of beta-2 agonist bronchodilators), at two points in time during the COVID-19 pandemic. Results:  Both groups had optimal control at baseline and at the end of the study, with a significant improvement in the last control (P < 0.05). In clinical manifestations there was no statistical difference (P > 0.05) in both controls. The mean ACT level of Fluticasone at discharge was significantly superior to Beclomethasone (P = 0.03). Conclusions: Teleconsultation is an effective tool for monitoring chronic diseases such as asthma. Both Fluticasone and Beclomethasone achieved optimal disease control, highlighting that the true determinant of good control is the continuous use of any ICG. However, a significant statistical difference was found in favour of Fluticasone; nevertheless, due to its lower price, the cost-effectiveness ratio favours Beclomethasone as a cost-effective and efficient option for optimal asthma control.